Respuesta :
Answer:
The expression is equivalent to 4 square root 6 divided by 3 root 2 is:
8/3
Step-by-step explanation:
Given expression:
4 square root 6 divided by 3 root 2
[tex]\frac{4\sqrt{6}}{3\sqrt{2} }[/tex]
[tex]=\frac{4\sqrt{2*2*2}}{3\sqrt{2} }[/tex]
[tex]=\frac{4\sqrt{2*2^{2} }}{3\sqrt{2} }[/tex]
square root of 2² = 2 hence,
[tex]=\frac{4*2\sqrt{2}}{3\sqrt{2} }[/tex]
[tex]=\frac{8\sqrt{2}}{3\sqrt{2} }[/tex]
Common terms in the numerator and denominator cancels each other out
[tex]=\frac{8}{3}[/tex]
By solving the expression using simple mathematical rules, we got an equivalent expression of
[tex]\frac{4\sqrt{6}}{3\sqrt{2} } = \frac{8}{3}[/tex]
Answer:
[tex]\frac{4\sqrt{3} }{3}[/tex]
Step-by-step explanation:
Find a common factor between the numerator and the denominator, so that they may cancel out one another.
[tex]\frac{4\sqrt{6} }{3\sqrt{2} } \\\\=\frac{4\sqrt{3*2} }{3\sqrt{2} } \\\\=\frac{4\sqrt{3}\sqrt{2} }{3\sqrt{2} }[/tex]
Then by cancelling out the square root of 2:
[tex]\frac{4\sqrt{3} }{3}[/tex]